GAME EDUKASI MENGENAL KEBUDAYAAN BANGSA BERBASIS ANDROID - Widayanto, Aprih; Saifudin, Saifudin; Julianto, Fajar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2023)
Abstracts - With so many foreign cultures entering and more and more people adapting foreign cultures, fewer people are familiar with the culture of the Indonesian people. Therefore, introducing national culture to the younger generation is very important to maintain and preserve national culture as the identity of the Indonesian nation. In this final project, an educational game called Petualangan Si Nau was developed with some assets made using Adobe Photoshop software and some downloaded from the Internet and the game engine used is Construct 2 software and does not use a special programming language because all commands used in the game are set. using EvenSheet which consists of Event and Action. The mechanism in the game developed is almost the same as platformer games in general, namely passing obstacles, collecting items, and achieving a goal at each level in the game. But the difference is, this game adds educational elements such as answering questions and so on. The educational game Petualangan Si Nau was built using the game engine Construct 2 and exported using the Cordova CLI, All the features contained in the educational game Petualangan Si Nau can function as expected, The educational game Petualangan Si Nau is a place or media to introduce traditional culture that exist in Indonesia to the younger generation, With the educational game Petualangan Si Nau students will find it easier to learn about traditional culture in Indonesia. Keywords: National Identity, Culture, Educational Games